THE EFFECTS OF LAND TENURE SECURITY ON LAND USE AND INVESTMENTS AMONG SMALL FARMERS IN THE BRAZILIAN AMAZON - Wood, Charles H.; Walker, Robert; Toni, Fabiano (Science & Technology Journals, 2001)
The idea that environmental degradation can be reduced by providing farmers with title to the land they work is the basis for numerous policy initiatives despite the paucity of supporting empirical evidence. This study uses a survey of titled and untitled landholders in the Brazilian Amazon to test the hypothesis that title ownership affects land uses decions and has a positive environmental effect. The findings show that titled farmers were more likely to use credit and apply fertilizers, as well as refrain from exploiting timber and engage in reforestation. These positive environmental outcomes were offset by evidence that titled farmers also deforested more land, purchased a greater number of cattle, and created larger pastures. We conclude that land titling has significant effects with respect to some types of behavior, but it should not be assumed that possession of land titles always leads to environmentally beneficial results.